1985
DOI: 10.1002/j.1460-2075.1985.tb03655.x
|View full text |Cite
|
Sign up to set email alerts
|

A split binding site for transcription factor tau on the tRNA3Glu gene.

Abstract: Yeast transcription factor tau forms a stable complex with tRNA genes. Using this property, the factor could be highly purified on a specific tDNA column. The purified factor was found by DNA footprinting to protect the whole yeast tRNA3Glu gene from position ‐8 to +81. A DNase‐sensitive site was retained in the middle of the gene on both strands. The 3′ border of the complex was mapped by exonuclease digestion at +88, just downstream of the termination signal. The 5′ limit of the complex was found at position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 40 publications
5
73
0
Order By: Relevance
“…The observed sequence context effects on Pol III termination at T 5 might in principle be mediated by TFIIIC, a transcription factor that usually covers a large part of the transcription unit, extending up to the terminator region of tRNA genes (37,38). TFIIICassociated activities have previously been proposed to influence Pol III termination in humans (39), and yeast TFIIIC has recently been shown to facilitate transcription reinitiation by Pol III on long transcription units (13).…”
Section: Distinguishing Between Weak and Strong T 5 Terminator Sequenmentioning
confidence: 99%
“…The observed sequence context effects on Pol III termination at T 5 might in principle be mediated by TFIIIC, a transcription factor that usually covers a large part of the transcription unit, extending up to the terminator region of tRNA genes (37,38). TFIIICassociated activities have previously been proposed to influence Pol III termination in humans (39), and yeast TFIIIC has recently been shown to facilitate transcription reinitiation by Pol III on long transcription units (13).…”
Section: Distinguishing Between Weak and Strong T 5 Terminator Sequenmentioning
confidence: 99%
“…Factor r purification and complex formation Factor r was purified according to Camier et al (1985) with the modifications recently described (Gabrielsen et al, 1989), which include a phosphocellulose adsorption step and heparin and DEAE-Sephadex chromatography, followed by affinity chromatography on a tDNA-agarose column. The purified factor preparation contained several polypeptide chains, two of which (145 and 100 kd) were shown to be involved in DNA binding (Gabrielsen et al, 1989).…”
Section: Plasmids and Dna Fragmentsmentioning
confidence: 99%
“…Yeast factor r and its interaction with tDNA have been extensively studied (Klementz et al, 1982;Ruet et al, 1984). Nuclease protection and methylation experiments (Camier et al, 1985;Stillman et al, 1985a), as well as point mutation analyses (Baker and Hall, 1984;Baker et al, 1986), have demonstrated the specific binding of r to the A and B blocks, the involvement of critical bases and the prominent role of the B block sequence in complex formation. Analysis of a series of tRNA3L&u gene recombinants having variable A to B distances have demonstrated the remarkable flexibility of i--DNA interaction (Baker et al, 1987;Fabrizio et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…TFIIIC contains an activity that binds to both the A and B regions in vitro (7,8,44) and remains bound through multiple rounds of gene transcription (3,17,34). Experiments with altered tRNA gene templates have shown that binding is primarily directed by the B block, although A block mutations lower the overall binding efficiency and drastically reduce promoter strength (2,7,31,44). The function of TFIIIB is unclear, although it has been shown to be necessary for the formation of stable preinitiation complexes in some cases (3).…”
mentioning
confidence: 99%